Taking the sting out of CRPS: bee venom to treat complex regional pain syndrome. Issue 1 (25th June 2016) - Brown, Zarah; Archer, Matt; Domos, Peter; White, Andrew
Summary: We describe the case of a 48‐year‐old right hand dominant male engineer diagnosed with complex regional pain syndrome 4 months following surgical repair of a distal biceps tendon rupture. He reported significant improvement in CRPS symptoms following an accidental bee sting and sought deliberate bee venom (apitoxin) inoculation to the affected limb. A single report in the literature describes the use of bee venom to treat CRPS in a human. The components of apitoxin include adolapin, melittin, apamin, phospholipase A2, histamine and protease inhibitors. Melittin and apamin have roles in synaptic transmission modulation and cell lysis. Adolapin inhibits cyclooxygenase and has analgesic, anti‐inflammatory and anti‐pyretic effects. Further research is required into the components of apitoxin as a potential treatment for CRPS.